Robust Army Aviation in Nepal for Services to the Country, People and Organization - Karki, Man Bahadur (Unity Journal, 2021)
Aviation is an essential mode of transport service because of the mountainous terrain in Nepal. Different parts of the country cannot be connected through a wide range of road network. Further, Nepal’s diverse geographical features, ranging from high hills to low wetlands appropriate airport transport. Nepal Army Aviation unit has immensely contributed to the organizational operational flights, emergency aerial rescue, relief, humanitarian services and nation’s development with the limited resources and infrastructure during its fifty–five years of journey in the air. After the adoption of liberal sky policy by the Government of Nepal in 1992, the private airlines commenced commercial air operations. Prior to this Nepal Airlines and Nepal Army Aviation unit were only the two entities operating inside the domestic airspace of Nepal. Despite the number of private air operators, there are still not enough and abundantly available air assets to fulfill all the requirements of air services especially in emergency aerial rescue, quick disaster response humanitarian assistance and relief flights in a short notice. Furthermore, there is a scope for the civil–military partnership in the civil aviation fi eld for the Nepal Army Aviation. This article, in efforts to make the Army Aviation agile, nimble and adoptable force multiplier for enhanced national security, examines its contributions in the service of country, people and organization as a state–owned institution with supports from secondary data.